2014
DOI: 10.5964/ijpr.v8i2.162
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Emotional Contagion: A Review of Classic and Recent Research on Facial Mimicry and Contagion

Abstract: Recently, scholars from a wide variety of disciplines, using a variety of scientific techniques, have begun to study the influence of attention, facial mimicry, and social context on emotional contagion. In this paper we will review the classic evidence documenting the role of attention, facial mimicry, and feedback in sparking primitive emotional contagion. Then we will discuss the new evidence which scholars have amassed to help us better understand the role of facial mimicry in fostering contagion and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(165 citation statements)
references
References 94 publications
(111 reference statements)
2
157
0
6
Order By: Relevance
“…Indirect emotional crossover relies on complex social behaviours that occupy a mediating position (Westman 2006)-a feature that most notably delineates crossover effects from predominantly automated mechanisms of immediate emotional contagion (Hatfield et al 2014). Contagious effects comprise of ubiquitous, culturally invariant tendencies of behavioural mimicry (see also Chartrand et al 2005), followed by afferent feedback.…”
Section: Mechanisms and Mediators Of Transmitting Enjoymentmentioning
confidence: 99%
“…Indirect emotional crossover relies on complex social behaviours that occupy a mediating position (Westman 2006)-a feature that most notably delineates crossover effects from predominantly automated mechanisms of immediate emotional contagion (Hatfield et al 2014). Contagious effects comprise of ubiquitous, culturally invariant tendencies of behavioural mimicry (see also Chartrand et al 2005), followed by afferent feedback.…”
Section: Mechanisms and Mediators Of Transmitting Enjoymentmentioning
confidence: 99%
“…It is a human tendency to inherently mimic a range of actions from vocal accents (Adank, Stewart, Connell, & Wood, ) to physical mannerisms (The Chameleon Effect; Chartrand & Bargh, ). Other studies also indicated that emotional mimicry (e.g., Hess & Fischer, ), a term describing the imitation of emotion, has been tied closely to the theory of primitive emotional contagion (Hatfield, Bensman, Thornton, & Rapson, ; see also Hatfield et al, ). This mimicry and feedback process may operate at a conscious level, but research has shown that this process is more automatic and unconscious than people think (Chartrand & Lakin, ).…”
Section: A Motivational Perspective On Social Contagionmentioning
confidence: 93%
“…Scholars from a variety of disciplines provide voluminous evidence that people do in fact frequently catch one another's emotions (see Hatfield, Bensman, Thornton, & Rapson, 2014;Hatfield, Cacioppo, & Rapson, 1994 for a review of this research). When people mimic expressions of fear, anger, sadness, joy, love, or disgust, they tend to feel not just any emotion (be it positive or negative) but a pale reflection of the specific emotions they have mirrored.…”
Section: Emotional Contagionmentioning
confidence: 99%